Narasi Berubah Pesan Moral Tetap: Transformasi Teks “Bhagawan Domya” ke dalam Cerita “Sang Eka Jala Resi” - I Wayan Cika; I Made Madia; Ni Wayan Arnati (Pusat Kajian Bali Universitas Udayana, 2021)
Transformation of classic stories, epics, or regional folklore into Indonesian is an important part of the history of literary life in Indonesia. This article discusses the transformation of the story of Bhagawan Domya in Adi Parwa which is part of the Mahabharata epic into Indonesian folklore entitled Sang Eka Jala Resi (1977/1978). The study focuses on the transformation process, the impacts of adapter’s receptions on the transformation process, as well as the existence of values ??in the source and the result texts. This qualitative study draws data from source and result texts and analyzed them with intertextuality and reception theories. The analysis shows that in the transformation process, adapters use various techniques including conversion, expansion, modification, and lacuna (removal). Even though there are changes during the transformation, moral values ??that are useful for character building in the Bhagawan Domya source text are still substantially the same in the Sang Eka Jala Resi result text.